Ruminal fermentation, methanogenesis and nitrogen utilization of sheep receiving tropical grass hay-concentrate diets offered with Sapindus saponaria fruits and Cratylia argentea foliage - Hess, H.D.; Beuret, RA; Lotscher, M; Hindrichsen, I.K.; Machmuller, A; Carulla, Juan E.; Lascano Aguilar, Carlos Eduardo; Kreuzer, M. (2004)
The effects of supplementing a tropical, low-quality grass hay (Brachiaria dictyoneura) with legume foliage (Cratylia argentea) or fruits of the multipurpose tree Sapindus saponaria on ruminal fermentation, methane release and nitrogen (N) utilization were evaluated. Six Swiss White Hill lambs were used in a 6 ? 6 Latin-square design with a 3 ? 2 factorial arrangement of treatments with measurements of energy metabolism being conducted using open-circuit respiratory chambers. Treatments consisted of three basal diets, either grass alone or legume : grass ratios of 1 : 2 or 2 : 1. These basal diets were supplemented (1 : 3) with a control concentrate or with a concentrate containing 250 g/kg dry matter of S. saponaria fruits. The apparent total tract digestibilities of organic matter (OM) and neutral-detergent fibre (NDF) were reduced and the proportionate crude protein (CP) losses through faeces were increased (P < 0·01) by supplementation with S. saponaria, and digestibilities of OM and NDF were linearly reduced (P < 0·001) with increasing legume proportion. Body energy retention, however, was similar in all diets. Along with CP intake, the proportionate CP losses through faeces decreased (P < 0·001) with increasing legume proportion which was associated with improved (P < 0·001) body protein retention and reduced (P < 0·1) fat retention. Ruminal fluid ammonia concentration was not significantly affected (P > 0·1) by the inclusion of S. saponaria in the concentrate, but increased linearly (P < 0·001) as dietary legume proportion was elevated. Supplementation with fruits of S. saponaria increased (P < 0·01) total bacteria count, and decreased (P < 0·001) total ciliate protozoa count by more than proportionately 0·50. Daily methane release was reduced (P < 0·01) by S. saponaria supplementation in all basal diet types. Although being not clearly affected on a daily basis, methane release relative to body protein retention decreased linearly (P < 0·05) with increasing legume proportion. The fact that interactions were mostly non-significant (P > 0·05) indicates that supplementation with S. saponaria fruits is a useful means to reduce methane emission from sheep given both tropical grass-based and grass-legume-based diets. Likewise, including legumes in N-limited tropical diets seems to represent an environmentally friendly way to improve animal productivity.